Enhanced bundle fiber displacement sensor based on concave mirror - Yang, Hang Zhou; Lim, Kok Sing; Harun, Sulaiman Wadi; Dimyati, Kaharudin; Ahmad, Harith (Elsevier, 2010)
Fiber optic displacement sensor (FODS) is proposed using a concave mirror for enhanced flexibility in sensitivity selection and linear range. The effect of focal length and diameter of the concave mirror on the displacement response is investigated. The experimental and theoretical results show that the second dip of the displacement response is located at distance equivalent to twice of focal length. For the third slopes and above, the sensitivity and the linear range of the sensor are strongly dependent on the focal length and diameter of the mirror. A good agreement between the theory and experimental results are shown. The measurement range as far as 26 mm can be achieved by using a 12 mm focal length concave mirror. (C) 2010 Elsevier B.V. All rights reserved.